The Role of Accounting in Managing Micro, Small and Medium Enterprises (MSMEs): The Case of Indonesia - Parulian Silaen; Steve Tulig (Australasian Accounting, Business and Finance Journal, 2023)
The Covid-19 pandemic affects the economy of a country as well as its Micro, Small, and Medium Enterprises (MSMEs). The MSMEs contribute to the economy of a country’s GDP and can engross the work force. In the case of Indonesia, 99% of MSMEs are micro and small business thatneeds an intervention program from the government. Having an Accounting skill is important to manage the MSMEs, as indicated by OECD report (2017) regarding the financial education. Unfortunately, the level of education that the owners of micro to small business have, are relatively low and therefore, the program should be developed carefully considering the educational background of the sector. Training these business owners on simple accounting skills which are critically important such as cash in and out records, may be suitable for micro and small business. In addition, recognition of their existence is also important by providing them a business certificate from the city council. The certificate can also be used as a basis to allocate temporary space for the business that do the trading in the street market. Having the certificate recorded and maintained by the city council as well as the simple financial record can be used by the government to base intervention program such as financial and skill training as well as access to financial support or loan.
Keywords: SME; MSME; ASEAN; Accounting skills for SME; Indonesia.